Molecular epidemiology and reverse transcript ase (RT) and protease inhibitors (PR) resistance genotyping of human immunodeficiency virus (HIV) in Kelantan - Rafidah Hanim, Shueb (Pusat Pengajian Sains Perubatan, 2012)
The wide use of antiretroviral (AR V) therapy has greatly reduced the rate of morbidity and mortality among Human immunodeficiency virus type- I (HIV -I) infected patients. However, high mutation and recombination rates of HIV -I lead to the emergence of various subtypes and drug-resistance viruses, rendering AR V -therapy ineffective in many patients. This study was undertaken to determine for the first time the prevailing HIV -I subtypes and the patterns of drug resistance mutations among 53 HIV -!-infected patients in Kelantan, Malaysia. Blood samples from 53 HIV-1 infected patients (naive and treated) were collected from Hospital Raja Perernpuan Zainab II, Kelantan, Malaysia from May 2009 to December 20 I 0. Protease (PR) and reverse transcriptase (RT) genes were amplified from patient plasma, and then sequenced and analysed for mutations. Subtype determination was done using NCB! Genotyping Tool while ARV resistance mutations were analysed using Stanford HIV Drug Resistance Database.